Critical Drivers in Public Sector Innovation: Governance and Service Insights from Yogyakarta and Kupang - Pradana, I Putu Yoga Bumi (UI Scholars Hub, 2025)
This study investigates the critical factors influencing the initiation of Public Sector Innovation (PSI) in Indonesia, focusing on governance and service-type innovations within two local government settings: Yogyakarta and Kupang. The methodology employed was a qualitative approach with multiple case studies complemented by the critical incident technique for data analysis. The data were gathered from 23 informants who played significant roles in the early stages of the innovation process at the local government level. The findings reveal that in Yogyakarta, the successful initiation of innovations such as Sego Segawe and YES 119 was primarily driven by robust political leadership, extensive external networks, and the availability of resources. In contrast, the innovations in Kupang, such as Kupang Green and Clean (KGC) and Brigade Kupang Sehat (BKS), were heavily influenced by strong collaboration with external stakeholders and the adaptability of innovations to local conditions. A comparative analysis of the two cases underscores that while both regions benefited from political support and external collaboration, the specific local context and available resources played a crucial role in shaping the innovation process. The novelty of this research lies in its cross-regional comparison, which provides new insights into how local contexts in different geographic regions of Indonesia influence the initiation and success of public sector innovations. These insights contribute to the broader PSI literature by highlighting the importance of contextual factors in successfully initiating public sector innovations in developing countries.